Kultura: Nový koncept rasy - Wikan, Unni (Lidé města, 2026)
In her article, Norwegian anthropologist Unni Wikan critically analyzes how the concept of culture is instrumentalized in Norwegian society and beyond to legitimize specific interests, acting as a euphemism for a new form of racism. The author contends that “culture” is frequently used in a reductionist manner to explain the behavior of immigrants, effectively rendering them passive objects stripped of autonomy. Wikan argues that this approach leads to the appropriation of the culture concept by both immigrants and Norwegian institutions, ultimately reinforcing stereotypes and deepening the marginalization of migrants. Furthermore, she critiques Norwegian immigration policy for being grounded in essentialist and utopian assumptions regarding respect, material support, and the static nature of identity. Calling for a paradigm shift in integration, Wikan emphasizes human rights and individual responsibility over cultural essentialism. She urges anthropologists to reflect on the power dynamics inherent in the concept of culture and to engage actively in public discourse. Ultimately, the text serves as a compelling call to critically reassess the role of culture within multicultural societies.